2003
DOI: 10.1159/000072851
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the molecular basis of polyglutamine neurodegeneration from studies of a spinocerebellar ataxia type 7 mouse model

Abstract: Spinocerebellar ataxia type 7 (SCA7) is one member of a growing list of neurodegenerative disorders that are all caused by CAG repeat expansions that produce disease by encoding elongated polyglutamine tracts in a variety of apparently unrelated proteins. In this review, we provide an overview of our efforts to determine the molecular basis of polyglutamine neurotoxicity in SCA7 by modeling this polyglutamine repeat disorder in mice. We discuss how our SCA7 mouse model develops a phenotype that is reminiscent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The presence of aggregates was shown to reduce the concentration of diffuse polyQ-expanded Htt and an increased neuronal survival [53]. It has been suggested that monomeric and oligomeric polyQ-expanded Htt protein exhibit cellular toxicity while formation of larger aggregates provides (at least temporary) protection from these toxic effects [52, 54]. These larger aggregates might eventually exhibit secondary pathogenic effects such as physically blocking vesicle or mitochondrial trafficking in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of aggregates was shown to reduce the concentration of diffuse polyQ-expanded Htt and an increased neuronal survival [53]. It has been suggested that monomeric and oligomeric polyQ-expanded Htt protein exhibit cellular toxicity while formation of larger aggregates provides (at least temporary) protection from these toxic effects [52, 54]. These larger aggregates might eventually exhibit secondary pathogenic effects such as physically blocking vesicle or mitochondrial trafficking in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The Sca7 gene that encodes Ataxin-7 is subject to polyglutamine (poly-Q) expansions in humans, giving rise to spinocerebellar ataxia (15). Mouse models of poly-Q expansions of Sca7 exhibit many phenotypes similar to those found in the human disease, including ataxia and retinal defects (15,43).…”
Section: Discussionmentioning
confidence: 99%
“…The Sca7 gene that encodes Ataxin-7 is subject to polyglutamine (poly-Q) expansions in humans, giving rise to spinocerebellar ataxia (15). Mouse models of poly-Q expansions of Sca7 exhibit many phenotypes similar to those found in the human disease, including ataxia and retinal defects (15,43). Current models suggest that the mutant proteins have adverse (17), but other studies indicate that poly-Q expanded Ataxin-7 proteins inhibit Gcn5 functions (25,30).…”
Section: Discussionmentioning
confidence: 99%
“…Spinocerebellar ataxia type 7 (SCA7) 4 is a dominantly inherited neurodegenerative disorder characterized by loss of neurons in the cerebellum, brain stem, and retina (1). SCA7 is a member of a family of neurodegenerative diseases in which a CAG DNA triplet repeat expansion results in polyglutamine expansion in the gene product (2).…”
mentioning
confidence: 99%